2019
DOI: 10.3390/cells8080778
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Ionizing Radiation Triggers Prolonged Changes in Circular RNA Abundance in the Embryonic Mouse Brain and Primary Neurons

Abstract: The exposure of mouse embryos in utero and primary cortical neurons to ionizing radiation results in the P53-dependent activation of a subset of genes that is highly induced during brain development and neuronal maturation, a feature that these genes reportedly share with circular RNAs (circRNAs). Interestingly, some of these genes are predicted to express circular transcripts. In this study, we validated the abundance of the circular transcript variants of four P53 target genes (Pvt1, Ano3, Sec14l5, and Rnf16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…PVT1 was reported to be involved in several central neuronal system diseases [ 29 , 30 ]. For instance, silence of PVT1 decreased the loss of neurons and inhibited the activation of astrocytes in hippocampus tissues of epileptic rats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…PVT1 was reported to be involved in several central neuronal system diseases [ 29 , 30 ]. For instance, silence of PVT1 decreased the loss of neurons and inhibited the activation of astrocytes in hippocampus tissues of epileptic rats [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that circRNA was associated with many biomarkers of ionizing radiation injury, such as mouse brain and primary neuron injury, mouse bone marrow injury, and radiation-related esophageal injury. 20 , 21 , 11 In addition, it is also found that circRNA is related to a variety of radiation diseases, such as hsa_circ_0001649 participating in the following regulation of migration and proliferation of cholangiocarcinoma cells after radiotherapy, and hsa_circRNA_ 100367 regulating radiosensitivity of esophageal cancer through Wnt pathway. 22 , 23 The miRNA is an evolutionary conservative small molecule with a length of 18–25 nucleotides.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to environmental pollution factors has been associated with defects during embryonic development as well as postpartum complications such as neonatal malformation and birth defects. Mfossa et al (2019) reported that exposure to ionizing radiation activated transcriptome of P53‐target genes to induce circular transcripts in mouse embryos and primary neurons. In response to radiation, expression of linear transcripts of P53 target genes peaked earlier than circRNAs in embryonic brain and primary cortical neurons.…”
Section: Circrnas In Embryogenesismentioning
confidence: 99%